THE EFFECT OF USING EXPERIMENTAL LKPD ON IMPROVING THE ABILITY TO OBSERVE AND BEHAVIOR IN CHOOSING SNACKS IN STUDENTS OF SMP NEGERI 1 GEMPOL - Anita Veronica; Zaenal Abidin; Anna Fitri Hindriana (Indonesian Journal of Learning and Instruction, 2025)
This research aims to analyze the effect of using the Student Worksheet (LKPD) for food additive content experiments on enhancing observation skills and healthy snack selection behavior of eighth-grade students at SMP Negeri 1 Gempol. The research employed a quantitative approach with pre-test post-test control group design, supported by a Mixed Methods concurrent embedded approach where qualitative data deepened the understanding of quantitative results. The experimental LKPD was developed using the ADDIE model. Data were collected through observation skills tests, healthy snack selection behavior questionnaires, and semi-structured interview. Statistical analysis included N-Gain scores and Mann-Whitney U tests. The results indicate that the experimental LKPD significantly improved students’ observation skills (p< 0.05, NGain 0.45). While the LKPD also positively influenced healthy snack selection behavior (N-Gain 0.14), the correlation between observation skills and behavior was weak and not statistically significant (r=0.207, p=0.148). This suggests that while cognitive skills improved, behavioral change is influenced by more complex factors. The study highlights the effectiveness of experimental LKPD with Diagram Vee in fostering scientific process skills and conceptual understanding, but also point to the need for holistic interventions to drive consistent behavioral changes related to food safety.